Synthesis a nd Characterization of Some New Transition Metal Complexes of Amino Thiadiazole - Numan, A.T; Jassim, l.Kh; Issa, l.O (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
New complcxcof Cu (ll),Ni(ll) ,Co(ll), and Zn(ll) wi th 2- amino-5-p-Fiouro Phenyl 1,3,4-Thiadiazole have been synthesized . The products were isolated , studied and characterized by physical measurements, i.e., (Ff -IR) ,UV-Vis and the melting points were determined .The new Schiff base (L) has been used to prepare some complexes .The prepared complexes were identified and their tructural geometry were suggested.